2019
DOI: 10.1039/c9ra04758a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antioxidant activities of fatty polyhydroquinolines synthesized by Hantzsch multicomponent reactions

Abstract: The insertion of a fatty long chain into polyhydroquinoline (PHQ) core contributes to antioxidant potential, the new fatty PHQs showed activities similar to commercial antioxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Following up on this perspective the cyclopentanone derivative 2-(hydroxy-(3-nitrophenyl)methyl)cyclopentanone (3NCP, Figure 1 ) [ 12 ] was evaluated as a possible potential candidate against AD. The inhibition of AChE and BChE , also the antioxidant activities has been attributed to the presence of the nitrophenyl group [ 13 , 14 , 15 , 16 , 17 ]. The ketone moiety exhibited dose-dependent antioxidant effects, which have been considered as a possible explanation for the decline of chronic neurodegenerative disorders like AD [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following up on this perspective the cyclopentanone derivative 2-(hydroxy-(3-nitrophenyl)methyl)cyclopentanone (3NCP, Figure 1 ) [ 12 ] was evaluated as a possible potential candidate against AD. The inhibition of AChE and BChE , also the antioxidant activities has been attributed to the presence of the nitrophenyl group [ 13 , 14 , 15 , 16 , 17 ]. The ketone moiety exhibited dose-dependent antioxidant effects, which have been considered as a possible explanation for the decline of chronic neurodegenerative disorders like AD [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional three-component reaction (3CR), the Hantzsch reaction allows 1,4-dihydropyridine skeleton (4) being accessed by treating 1,3-cyclohexanedione (1), o-nitrobenzaldehyde (3), and oleyl acetoacetate (2) with ammonium salt as shown as equation (1) in Figure 1. The imine moiety (NÀ H) in 4 is able to quench 2,2-diphenyl-1-picrylhydrazyl radical (6, DPPH) as phenolic -OH in α-tocopherol does, [10] and it is also found that the ability of 5 to scavenge DPPH is similar to that of α-tocopherol even though -NO 2 (an electron-withdrawn group, EWG) is contained. [11] This is attributable to the aromatization of 1,4-dihydropyridine for producing pyridine skeleton, while the long aliphatic chains in 4 and 5 might be beneficial for the bioavailability.…”
Section: Hantzsch Reactionmentioning
confidence: 99%
“…The Hantzsch 3CR exemplifies such a protocol that multiple antioxidative features can be efficiently integrated into one molecule for accessing to an antioxidant with multifunctional groups. As shown as equation 2of Figure 1, 8 performs the aminolysis with melatonin (7) to afford 9 as the reagent for the following Hantzsch 3CR with m-bromobenzaldehyde (10) and (NH 4 ) 2 CO 3 , and the produced 1,4-dihydropyridine in 11 exhibits the oxygen radical absorbance capacity (ORAC = 8.78) even 3~fold higher than melatonin (7, ORAC = 2.45) because of contributions from both double melatonin and 1,4dihydropyridine skeletons in 11 simultaneously. [12]…”
Section: Hantzsch Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally known as one of the main groups of nitrogen heterocycles, polyhydroquinolines (PHQs) and polyhydroacridines (PHAs) have become considerably interesting due to their significant therapeutic and pharmacological properties 97 – 100 . Indeed, they are used as antimalaria, calcium β-blocker, antioxidant, antimicrobial, antifungal, vasodilator, anticancer, bronchodilator, antiatherosclerotic, geroprotective, hepatoprotective and antidiabetic agents as well as in the production of laser colors, radical reservoirs and safe hydrogen transfer agents 4 , 101 111 . First introduced by Arthur Hantzsch in 1882, Hantzsch reaction is an MCR that contains the combination of a β-dicarbonyl compound, an aldehyde and a source consisting of ammonia (usually NH 4 OAc) 112 .…”
Section: Introductionmentioning
confidence: 99%